2023
DOI: 10.3390/constrmater3040024
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Mechanical Properties of Polymer-Stabilized Rammed Earth Construction

Salih Kocak,
Aneurin Grant

Abstract: This paper investigates the viability of using a commercially available liquid polymer (LP) in lieu of ordinary cement to stabilize soil during rammed earth (RE) construction. The scope of this study includes modifying and testing the locally available natural soil with two different LPs at various percentages. Once the optimum moisture content (OMC) of the soil with LPs was determined using the Proctor test, test samples were prepared by chemical and mechanical stabilizations. Following the curing process in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…In a study [22], UCS and curing time of the soil were enhanced so that the studied polymer (vinyl acetate-ethylene) stabilized the clay samples through a pore-filling effect, physicochemical bonds, and surface wrapping. Kocak and Grant [23] implemented a commercially available liquid polymer instead of ordinary cement to assess soil stabilization during rammed earth construction. They reported that the CBR and UCS values of polymer-stabilized soils were improved up to 10 and 3 times, respectively, compared to untreated samples.…”
Section: Ucs Testsmentioning
confidence: 99%
“…In a study [22], UCS and curing time of the soil were enhanced so that the studied polymer (vinyl acetate-ethylene) stabilized the clay samples through a pore-filling effect, physicochemical bonds, and surface wrapping. Kocak and Grant [23] implemented a commercially available liquid polymer instead of ordinary cement to assess soil stabilization during rammed earth construction. They reported that the CBR and UCS values of polymer-stabilized soils were improved up to 10 and 3 times, respectively, compared to untreated samples.…”
Section: Ucs Testsmentioning
confidence: 99%
“…To mitigate the effects of fungal growth on the durability of earth constructions, it is possible to modify a combination of mixtures, reduce moisture, and ensure the maintenance of the building [19]. Lime, fly ash, cement, polymers, and red clay binders with epoxy emulsion have been used as additives to improve the properties of soils against water erosion [20][21][22][23][24][25]. Moreover, reducing clay content in mixtures has proven effective [26,27].…”
Section: Introductionmentioning
confidence: 99%